Systematic literature review on the application of the life cycle sustainability assessment in agricultural production - Abdul Rahman, Mohammad Hariz; Sharaai, Amir Hamzah; Ponrahono, Zakiah; Nik Ab Rahim, Nik Nor Rahimah; Abu Bakar, Nurul Ain; Hanifah, Nurul Atilia Shafienaz; Md Suptian, Mohd Fairuz; Zubir, Mohd Nizam; Ahmad Shafawi, Norsyuhaida (Hapres Limited, 2024)
This article highlights the implementation of the Life Cycle Sustainability Assessment (LCSA) in the agricultural industry and its potential for future improvement. A systematic literature review was employed, whereby a total of 186 articles on the LCSA across all sectors were analysed. Of these, 22 (12%) were related to the agricultural sector and studied further to ascertain the methodology used, including the techniques used to define sustainability. In addition, the integration of current LCSA approaches and various methods of measuring sustainability were explored to provide a more comprehensive technique to define sustainability. Within each specific context, environmental issues like climate change, air quality deterioration, and eutrophication were among the indicators of interest, together with high production costs (economic) and issues related to workers and local communities (social). For the benefit of future researchers, the authors also discussed the challenges and prospects of adopting new technologies such as the use of artificial intelligence for effective implementation of sustainability assessment in the agricultural sector.